Optimization of pH to Bacteriocin Production by Lactic Acid Bacteria Growol Isolate Against Salmonella typhi - Afaroh, Firda Rizka; Suryani , Lilis (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Introduction – Growol is a traditional food from Yogyakarta which made from fermentation by Lactid Acid Bacteria (LAB) of cassava. LAB growol isolate as probiotics have ability to produce bacteriocins. Bacteriocins are useful for eradicating gram-positive and negative pathogenic bacteria. Bacteriocin activity is influenced by many factors, including pH, temperature, incubation time, and others, but the research about optimization of pH to produce bacteriocins that have maximum activity against S. typhi bacteria has been very limited. Purpose – This study aims to determine the ability of the bacteriocins produced by LAB growol isolate to inhibit the growth of S. typhi bacteria and to optimize the pH of the culture to increase its activity. Methodology/Approach – This research used a quasi-experimental method using post control group design. There were 5 samples of S. typhi bacteria which were divided into 5 groups. Group 1 was used as normal control without pH treatment. Groups 2, 3, 4, 5 were treatment with pH 2; 4; 6; 8. Each pH treatment was carried out with 4 repetitions. After the treatment, diameter of the inhibition zone of the disc was measured. The data obtained processed were using anova as a statistical analysis to see the difference in the sample mean. Findings – This study showed the results that optimizing of pH bacteriocin was optimum at inhibiting the growth of S. typhi bacteria is 2 with average diameter of inhibition zone is 11.10 mm. Originality/ Value/ Implication – The results of this study prove that pH has ability to affects bacteriocin activity produced by LAB growol isolate against S. typhi. LAB growol isolate has potential to produce bacteriocins to kill S. typhi.